Предмет: Математика, автор: alinatatarenko2007

(х+1)(х²-2х+5)+(х²+3)(1-х) равно 8

Ответы

Автор ответа: elena20092
1

Ответ:

х = 1

Пошаговое объяснение:

(х + 1) (х² - 2х + 5) + (х² + 3)(1 - х) = 8

х³ + х² - 2х² - 2х + 5х + 5 - (х² + 3 - х³ -3х) = 8

х³ - х² + 3х + 5 - х² - 3 + х³ +3х - 8 = 0

2х³ - 2х² + 6х - 6 = 0

2х²(х - 1) + 6(х - 1) = 0

х²(х - 1) + 3(х - 1) = 0

(х - 1)(х² + 3) = 0

1) х - 1 = 0  ⇒  х = 1

2) х² + 3 ≠ 0 и всегда положительно.

Похожие вопросы
Предмет: Геометрия, автор: brenkulskairyna